PENERAPAN PIVOTAL RESPONSE TREATMENT TERHADAP KEMAMPUAN JOINT ATTENTION PADA ANAK AUTIS - Rahmah, Hidayatur (Jurnal Pendidikan Khusus, 2017)
ABSTRACT One of the disturbances in communication which was early diagnosed to children with autism was that there was disturbance in joint attention ability. The less of joint attention ability to children with autism would make them difficult to interact with the others, they often appeared busy with themselves, they were difficult to divide or generalize attention with the other people, difficult to share emotion with the other people, and less contact eyes, and they could not follow the gesture direction from other people. In this research, the researcher arranged the activity which had purpose to develop joint attention ability to children with autism using pivotal response treatment.        This research used quantitative approach with pre experimental design kind of research and one group pretest-posttest design. This research was done in TK Mentari School Sidoarjo with 6 children with autism around 4-7 years old as the research subject. Based on the result of data analysis about joint attention ability to children with autism before giving treatment (pre-test) it was obtained average value 34,17 and after giving treatment (post-test) using pivotal response treatment it was obtained average value 80,83. From the counting result using sign test it was obtained Zh = 2,05 greater than critic value = 1,96 (two sides test) so Ho was refused and Ha was accepted. So, the result of data analysis indicated that there was influence of pivotal response treatment application toward joint attention ability to children with autism.   Keywords: Joint Attention Ability, Pivotal Response Treatment.